2020
DOI: 10.1186/s12891-020-03378-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of open ankle dislocation without associated fractures in a young athlete using external fixation and ligament repair with suture tape augmentation

Abstract: Background: Ankle dislocation without fracture is an extremely rare injury because it is usually accompanied by concomitant malleolar fractures from the anatomical and mechanical viewpoints. Case presentation: We report the case of a 17-year-old woman who was injured while playing basketball. Her ankle was swollen and deformed. Plain X-ray revealed tibiotalar dislocation in the medial direction without any fractures. Immediate reduction and ligament repair using suture tape augmentation were performed. Conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…The repair of the lateral ligament is the most controversial issue especially in open injuries. 5,7,8,10 Elise et al recommended an acute repair in open injuries. 11 In contrast, in the systematic review of Wight et al, acute ligament repair has been done in 26% and they concluded that it didn't influence ankle instability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The repair of the lateral ligament is the most controversial issue especially in open injuries. 5,7,8,10 Elise et al recommended an acute repair in open injuries. 11 In contrast, in the systematic review of Wight et al, acute ligament repair has been done in 26% and they concluded that it didn't influence ankle instability.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors recommend immobilization with non-weight bearing of a mean period of 6 weeks, while others described some cases with good outcome after progressive mobilization with full weight bearing after only 2 weeks. 1,7 Those who preferred shorter duration of immobilization considered that this will decrease the incidence of stiffness, which is the most common complication of pure ankle dislocation. 1,7 On the other hand, the choice of the immobilization device didn't prove to affect ankle stiffness or instability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 There was a large open wound with grossly exposed bones happened at farmer's field with a high risk of infection, accompanied by extensive soft tissue swelling so we decided to do reduction by delta frame external fixator in comparison to the other reported treatment option like reduction followed by casting. 6,7,9 Subsequently patients improved without infection postoperatively. Due to insufficient study, the outcome of ligament repair is controversial and the reported reports also support the outcome not affected by ligament repair for which reason we did not perform ligament repair.…”
Section: Case Reportmentioning
confidence: 91%